PREGNANCY RELATED PLASMA PROTEIN–A AND PREMATURE BIRTH - Iv. Todorov; N. Tododrov; M. Angelova; K. Peeva (Trakia Journal of Sciences)
Introduction: Children born prematurely are at higher risk of mortality, morbidity, and impaired motor and cognitive development in childhood than prematurely born babies. Aim: To establish the relationship between the corresponding levels of pregnancy-related plasma protein-A (PAPP-A) and the frequency of premature birth. Materials and methods: The study is prospective. The data was collected through monitoring patients through a questionnaire and sonographic examination at 11-13 gestational weeks. The study excluded all known risk factors for preterm birth, such as previous preterm births, pregnant women with gestational diabetes, preeclampsia, hypertension, placenta previa, hydramnion, multiple pregnancies, smoking, structural and chromosomal abnormalities of the fetus and planned preterm birth. The data from the measured values of PAPP-A and the frequency of premature birth in 636 pregnant women were analyzed. Conclusions: PAPP-A levels are a statistically significant factor for preterm birth. It is expected with a 95% probability in the population with PAPP-A values below 0,515 that the cases with premature birth will be from 7 to 14 times more. Pregnant women with PAPP-A level less than 10th per cent are significantly associated with an increased risk of preterm birth.